On Cacopsylla moiwasana (Kuwayama, 1908) (Hemiptera: Psylloidea: Psyllidae) associated with Sorbus (Rosaceae) with new synonymies - Cho, Geonho; Inoue, Hiromitsu; Lee, Seunghwan (Zootaxa, 2019)
New junior synonyms are proposed for the Sorbus-feeding Cacopsylla moiwasana (Kuwayama, 1908): Psylla jezoensis Miyatake, 1963, syn. nov. and Psylla midoriae Miyatake, 1963, syn. nov. The species is newly recorded from Korea.